Left ventricular systolic function in subjects conceived through assisted reproductive technologies - Sciuk, Franziska; Vilsmaier, Theresa; Kramer, Marie; Langer, Magdalena; Kolbinger, Brenda; Li, Pengzhu; Jakob, André; Rogenhofer, Nina; Dalla-Pozza, Robert; Thaler, Christian; Haas, Nikolaus Alexander; Oberhoffer, Felix Sebastian (Frontiers in Cardiovascular Medicine, 2023)
Background: Over the past decades, assisted reproductive technologies (ART) have gained remarkable influence in the treatment of infertility and account for more than 2% of births in European countries nowadays. Accumulating evidence suggests ART to cause cardiovascular alterations, including left ventricular (LV) dysfunctions, within its offspring. The aim of this study was to assess LV systolic function in subjects conceived through ART in comparison to spontaneously conceived peers. Methods: For the assessment of LV morphology and LV function, M-Mode echocardiography, pulsed wave Doppler and two-dimensional speckle tracking echocardiography (2DSTE) were applied. LV ejection fraction (EF) and fractional shortening (FS) were assessed in M-Mode and calculated by Teichholz formula. EF was additionally assessed semiautomatically through 2DSTE. Results: In total, 64 ART subjects and 83 spontaneously conceived controls with no significant differences in age (12.52 ± 5.64 years vs. 13.20 ± 5.95 years, p=0.486) and sex were included in the analysis. In the ART cohort, significantly lower values were observed for M-Mode assessed EF (63.63 ± 5.17 % vs. 65.35 ± 5.10 %, p=0.046) and FS (34.26 ± 3.87 % vs. 35.60 ± 3.84 %, p=0.038). However, after the adjustment for birth weight percentile and gestational age, M-Mode assessed EF and FS displayed no significant differences between both groups. LV morphology and remaining systolic function parameters, such as mitral annular plane systolic excursion, aortic velocity time integral, global peak longitudinal strain and 2DSTE measured EF, were comparable between both groups. Conclusion: This study suggests a lower LV systolic function in ART subjects, visualized by significantly lower values for M-Mode assessed EF and FS, compared to spontaneously conceived peers. The clinical relevance of these findings has to be investigated as the above-mentioned parameters were in normal reference range. In addition, LV systolic function parameters evaluated by other echocardiographic imaging modalities were comparable between both groups. Therefore, further studies will be required to evaluate the influence of ART on LV systolic function and cardiovascular morbidity in the future.